(untitled) (Malaysian Journal of Learning and Instruction, 2017)
Purpose – This study examines the effect using GeoGebra dynamic geometry software on students’ ability to confront geometry problem solving, their achievement in spatial visualization skills, and their usage of cognitive skills in applying, analyzing, evaluating, creating and constructing ideas for geometry problem solving on the topic of Shape and Space towards supporting 21st century learning of Mathematics Education. Methodology – Quantitative and qualitative data were collected for this study. A total of 102 Form Two students participated in the study, which had employed the pre-test and post-test quasi-experimental research design. The research participants were divided into three groups, namely Experimental Group 1 (n=33), Experimental Group 2 (n=35) and Control Group (n=34). A guideline book on using GeoGebra dynamic geometry software in learning of Shape and Space, developed by the researchers and validated by a panel of experts, was used by the teachers and students in the experimental groups. The quantitative data, obtained via the Topical Test (TT) and Spatial Visualization Ability Test (SVAT), were analysed using MANOVA. The reliability coefficients of TT and SVAT were 0.972 and 0.953 respectively. The qualitative data, collected via interviews, teaching observations, video recordings and students’ works, was thematically analysed. Findings – The experimental groups’ TT and the SVAT post-test mean scores for both the experimental groups were significantly higher than the control group’s TT and the SVAT post-test mean scores. The learning of Shape and Space using GeoGebra dynamic geometry software had enabled students to produce works with evidence of critical, creative and innovative elements in their solutions. The experimental groups’ students agreed that using the dynamic software something new to them and was indeed as an attractive way to learn mathematics because they had the opportunity to experience hands-on learning of mathematics using ICT. They voiced their dessire to also use the GeoGebra dynamic geometry software when learning other mathematics topics. Significance – The use of GeoGebra dynamic geometry software to support the notion of integration of technology in the teaching and learning of mathematics in schools has the potential to promote active students involvement in mathematics learning. The active learning could provide students with meaningful learning experiences and opportunities to produce quality, creative and innovative works. The dynamic software has the capacity to support students’ logical and systematic approaches in solving geometry problems and also triggers multiple ways of interactions and collaborations in the mathematics classrooms. The stimulation of students’ creative and innovative thinking provide evidence for the potential support of the dynamic software towards realizing 21st century learning within Mathematics Education.